The role of the amygdala during emotional processing in Huntington's disease: From pre-manifest to late stage disease - Jiaxiang Zhang (Neuropsychologia, 2015)
BackgroundDeficits in emotional processing can be detected in the pre-manifest stage of Huntington's disease and negative emotion recognition has been identified as a predictor of clinical diagnosis. The underlying neuropathological correlates of such deficits are typically established using correlative structural MRI studies. This approach does not take into consideration the impact of disruption to the complex interactions between multiple brain circuits on emotional processing. Therefore, exploration of the neural substrates of emotional processing in pre-manifest HD using fMRI connectivity analysis may be a useful way of evaluating the way brain regions interrelate in the period prior to diagnosis.MethodsWe investigated the impact of predicted time to disease onset on brain activation when participants were exposed to pictures of faces with angry and neutral expressions, in 20 pre-manifest HD gene carriers and 23 healthy controls. On the basis of the results of this initial study went on to look at amygdala dependent cognitive performance in 79 Huntington's disease patients from a cross-section of disease stages (pre-manifest to late disease) and 26 healthy controls, using a validated theory of mind task: “the Reading the Mind in the Eyes Test” which has been previously been shown to be amygdala dependent.ResultsPsychophysiological interaction analysis identified reduced connectivity between the left amygdala and right fusiform facial area in pre-manifest HD gene carriers compared to controls when viewing angry compared to neutral faces. Change in PPI connectivity scores correlated with predicted time to disease onset (r=0.45, p<0.05). Furthermore, performance on the “Reading the Mind in the Eyes Test” correlated negatively with proximity to disease onset and became progressively worse with each stage of disease.ConclusionAbnormalities in the neural networks underlying social cognition and emotional processing can be detected prior to clinical diagnosis in Huntington's disease. Connectivity between the amygdala and other brain regions is impacted by the disease process in pre-manifest HD and may therefore be a useful way of identifying participants who are approaching a clinical diagnosis. Furthermore, the “Reading the Mind in the Eyes Test” is a surrogate measure of amygdala function that is clinically useful across the entire cross-section of disease stages in HD.